Trends in telemedicine use in addiction treatment - Molfenter, Todd (Addict Sci Clin Pract, 2015)
INTRODUCTION: Telemedicine use in addiction treatment and recovery services is limited. Yet, because it removes barriers of time and distance, telemedicine offers great potential for enhancing treatment and recovery for people with substance use disorders (SUDs). Telemedicine also offers clinicians ways to increase contact with SUD patients during and after treatment. CASE DESCRIPTION: A project conducted from February 2013 to June 2014 investigated the adoption of telemedicine services among purchasers of addiction treatment in five states and one county. The project assessed purchasers’ interest in and perceived facilitators and barriers to implementing one or more of the following telemedicine modalities: telephone-based care, web-based screening, web-based treatment, videoconferencing, smartphone mobile applications (apps), and virtual worlds. DISCUSSION AND EVALUATION: Purchasers expressed the most interest in implementing videoconferencing and smartphone mobile devices. The anticipated facilitators for implementing a telemedicine app included funding available to pay for the telemedicine service, local examples of success, influential champions at the payer and treatment agencies, and meeting a pressing need. The greatest barriers identified were: costs associated with implementation, lack of reimbursement for telemedicine services, providers’ unfamiliarity with technology, lack of implementation models, and confidentiality regulations. This paper discusses why the project participants selected or rejected different telemedicine modalities and the policy implications that purchasers and regulators of addiction treatment services should consider for expanding their use of telemedicine. CONCLUSIONS: This analysis provides initial observations into how telemedicine is being implemented in addiction services in five states and one county. The project demonstrated that despite the considerable interest in telemedicine, implementation challenges exist. Future studies should broaden the sample analyzed and track technology implementation longitudinally to help the research and practitioner communities develop a greater understanding of technology implementation trends and practices.